Chemical composition and antibacterial activity of Berberis vulgaris (barberry) against bacteria associated with caries. Issue 4 (15th December 2020) - Kazemipoor, Maryam; Fadaei Tehrani, Pooya; Zandi, Hengameh; Golvardi Yazdi, Reza
Abstract: Objectives: The aim of this in‐vitro study was to determine the antimicrobial capacity of a Berberis vulgaris plant extract on the bacteria being associated with caries including, Streptococcus mutans, S . sobrinus, S . sanguinis, S . salivaris and Lactobacillus rhamnosus . Material and methods: Chlorhexidine 2% (CHX) mouthwash and ampicillin (10 μg/disk) were applied as positive control groups. Inhibition zone, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) related to stem, leaf and fruit of B . vulgaris plant were recorded for every five bacteria. Data were analyzed using SPSS ver. 22, one‐way ANOVA repeated measure and post hoc Tukey statistical test. The significance level was set at p < 0.05. Results: There were no significant differences between the antimicrobial capacity of the positive controls and the extract from the stem and fruit of B . vulgaris ( p > 0.05). The MIC values of the extract from the stem were significantly lower against S . sobrinus (64 μg/ml) and L . rhamnosus (128 μg/ml). The MIC value of the extract against S . mutans was significantly lower in the fruit group (64 μg/mL). The MBC value of the extract against S . sobrinus and L . rhamnosus was significantly lower in the stem group (128 μg/ml). The MBC value against S . mutans was significantly lower in the fruit group (128 μg/ml). Conclusions: The results showed that CHX and B . vulgaris plant extract have similar antimicrobial activity against bacteria being associated with caries. Therefore, B . vulgaris, which shows antibacterial capacity, could be considered for further investigation as a safe, phytotherapeutic mouthwash to prevent dental caries.